Higher education community engagement projects at local museums (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The University of Pretoria, South Africa, presents a compulsory undergraduate module, Community-based Project (code: JCP) in the Faculty of Engineering, Built Environment and Information Technology. It entails students working for at least 40 hours in the community, and then reflecting on their experiences through various assignments, including a presentation, a report and a YouTube video. A large number of students are enrolled in the module each year. Projects vary from basic renovation and building projects to the teaching of Mathematics and Science, repairing old computers for schools and non-profit organisations, and teaching community members basic computer skills. A number of projects are also taking place at local museums and other historical sites. This servicelearning-related course aims to make students more aware of their social responsibility and to teach them soft skills, for example, communication, leadership and time management skills.
Keywords: University of Pretoria; Service learning; Community-based Project Module; JCP module; Museums